POLISI WANITA (POLWAN) DI SUMATERA BARAT (1948-2013) SUATU STUDI HISTORIS KOMPARATIF - Handayani, Revi (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
This paper aims to know the policewomen histories which are part of the Indonesian National Police institution and the role of policewomen in the Indonesian National Police institution. This paper also described the recruitment, the education, and the challenges to become a policewoman in 1948 then the writer observed the changes in 2013. This paper had used the historical research methods that were the heuristics (data collection), the criticism sources (external and internal), the interpretation (analysis) and the historiography. In this paper, the writer used the sources from the library research and the archives. Apart from the written sources, the writer also obtained the data through the oral sources by interviewing the people who knew about the assignment, the career, the recruitment of the policewomen in West Sumatra. In this paper, the writer found the presence of women as the policewomen had a positive impact on the police. Research can represent gender equality and the existence of women as public servants who are usually identical to men, even though in reality there is a dichotomy between women and men. This study provides a general conclusion that the current gender problems that occur for women in 2013 are very concerned, this can be seen from the increasing acts of violence against women, overcoming this problem. Policewomen are here to face the problem. However, the idea of the emergence of Polwan aims to minimize violence against women and provide comfort to women who are involved in crime. If victims of crime, namely women, must be examined or searched by men, it will provide inconvenience and vulnerability to abuse, then the Policewoman is here. As the zeitgeist and the increasingly massive voicing of policewomen's gender equality become a profession that is no longer taboo, Policewomen are present in the Police to give a gentle impression and energy and far from the impression of violence. Keywords: Gender, Policewomen, Comparative History.